COMBINED APPLICATION OF MICRONUTRIENTS AND STAKE DIPPING OF CASSAVA FOR ALLEVIATING THE DEFICIENCY AND MAXIMIZATION OF TUBER YIELD - M.VELMURUGAN (Journal of Animal and Plant Sciences, 2024)
Cassava is one among the important tuber crop cultivated globally which requires heavy application of organic manures, fertilizers and micronutrients. Cassava is severely prone to micro nutrient deficiencies, more especially the iron induce chlorosis which is noticed invariably in all the soil types. The plants died due to acute micronutrient deficiency causing the drastic crop loss. Considering the acute need of cassava growers, this experiment was conducted over three seasons to determine the effect of combined application of micronutrients and stake dipping for improving the yield of cassava tubers and starch content. The experiment was layout in Randomized Complete Block Design (RCBD), with eight treatments repeated three times in plot size of 4.5x4.5 m for three seasons and between 2022 and 2024, the best treatment was validated through large scale demonstrations in farmers field. The recommended dose of NPK was applied three months after planting and the micronutrients viz., borax, magnesium sulphate and zinc sulphate were applied between one and two months after planting. In addition to the above, dipping the setts (stakes) in ferrous sulphate solution for a period of fifteen minutes before planting and subsequently three to four times of foliar application with 0.5% Ferrous sulphate solution at an interval of weeks times and also on visualization of the deficiency symptoms. The experimental results revealed that the number of tubers (9.53), lengthiest tuber (35.05 cm), maximum tuber girth (19.37), tuber yield (3.42 kg plant-1), starch content of tubers (24.60%) and maximum BC ratio (3.66) were recorded in RCP + dipping the setts (stakes) in 0.5% of FeSO4 solution + combined application of micronutrients in soil: MgSO4 (20 kilograms per hectare) + ZnSO4 (12.5 kilograms per hectare) + Borax (10 kilograms per hectare) (T7). The highest tuber dry weight (0.729 kg plant-1) was recorded in the same treatment. This treatment did not produce any micronutrient deficient plants and found to be highly economical to the cassava growers. However, the differential application of micronutrients did not influenced the HCN content of tubers.
Keywords: Cassava; micro nutrient; stake dipping; starch content; tuber yield